Real-time smooth trajectory generation for nonholonomic mobile robots using Bézier curves - Renny Simba, Kenneth; Uchiyama, Naoki; Sano, Shigenori (Robotics and computer-integrated manufacturing, 2016)
This paper focuses on generating smooth trajectories for a wheeled nonholonomic mobile robot using piecewise Bézier curves with properties ideally suited for this purpose. The developed algorithm generates smooth motion trajectories with C2 continuous curvature. We consider a teleoperated wheeled mobile robot in an indoor environment with ceiling cameras for operator visibility. The motion trajectory is constrained by the operator-specified via points and path width. A method to automatically generate a trajectory based on only these two inputs is proposed and demonstrated. To improve the trackability of the mobile robot, we adopted a Bézier subdivision method and inserted a quintic Bézier segment into high-curvature areas. The proposed algorithm can be used for real-time obstacle-avoidance trajectory generation because it allows trajectory subdivision and arbitrarily setting of the second derivative at the start point. Simulation and experimental results demonstrate the effectiveness of the proposed method. •New algorithm to generate smooth trajectories for a wheeled mobile robot.•Trajectory generation satisfying operator-specified via points and path width.•Trackability enhancement to high-curvature trajectory by Bezier subdivision method.•Design of a trajectory tracking controller based on the Lyapunov stability theorem.